Extra‐hepatic morbidity and mortality in alcohol‐related liver disease: Systematic review and meta‐analysis. (5th February 2023) - Theodoreson, Mark D.; Aithal, Guruprasad P.; Allison, Michael; Brahmania, Mayur; Forrest, Ewan; Hagström, Hannes; Johansen, Stine; Krag, Aleksander; Likhitsup, Alisa; Masson, Steven; McCune, Anne; Rajoriya, Neil; et al.
Abstract: Background: Alcohol use increases the risk of many conditions in addition to liver disease; patients with alcohol‐related liver disease (ALD) are therefore at risk from both extra‐hepatic and hepatic disease. Aims: This review synthesises information about non‐liver‐related mortality in persons with ALD. Methods: A systematic literature review was performed to identify studies describing non‐liver outcomes in ALD. Information about overall non‐liver mortality was extracted from included studies and sub‐categorised into major causes: cardiovascular disease (CVD), non‐liver cancer and infection. Single‐proportion meta‐analysis was done to calculate incidence rates (events/1000 patient‐years) and relative risks (RR) compared with control populations. Results: Thirty‐seven studies describing 50 302 individuals with 155 820 patient‐years of follow‐up were included. Diabetes, CVD and obesity were highly prevalent amongst included patients (5.4%, 10.4% and 20.8% respectively). Outcomes varied across the spectrum of ALD: in alcohol‐related fatty liver the rate of non‐liver mortality was 43.4/1000 patient‐years, whereas in alcoholic hepatitis the rate of non‐liver mortality was 22.5/1000 patient‐years. The risk of all studied outcomes was higher in ALD compared with control populations: The RR of death from CVD was 2.4 (1.6–3.8), from non‐hepatic cancer 2.2 (1.6–2.9) and from infection 8.2 (4.7–14.3). Conclusion: Persons with ALD are at high risk of death from non‐liver causes such as cardiovascular disease and non‐hepatic cancer.